Elucidation of Cellular Responses in Non-human Primates With Chronic Schistosomiasis Followed by Praziquantel Treatment - Melkus, Michael W.; Le, Loc; Siddiqui, Arif J.; Molehin, Adebayo J.; Zhang, Weidong; Lazarus, Samra; Siddiqui, Afzal A. (Frontiers in Cellular and Infection Microbiology, 2020)
For decades, mass drug treatment with praziquantel (PZQ) has been utilized to treat schistosomiasis, yet reinfection and the risk of drug resistance are among the various factors precluding successful elimination of schistosomiasis. Tractable models that replicate “real world” field conditions are crucial to effectively evaluate putative schistosomiasis vaccines. Herein, we describe the cellular immune responses and cytokine expression profiles under field conditions that include prior infection with schistosomes followed by treatment with PZQ. Baboons were exposed to S. mansoni cercariae through trickle infection over five weeks, allowed for chronic disease to develop, and then treated with PZQ. Peripheral blood mononuclear cells (PBMCs) were monitored for cellular immune response(s) at each disease stage and PZQ therapy. After initial infection and during chronic disease, there was an increase in non-classical monocytes, NK and NKT cells while the CD4:CD8 T cell ratio inverted from a 2:1 to 1:2.5. The cytokine expressions of PBMCs after trickle infections were polarized more toward a Th2 response with a gradual increase in Th1 cytokine expression at chronic disease stage. Following PZQ treatment, with the exception of an increase in B cells, immune cell populations reverted back towards naïve levels; however, expression of almost all Th1, Th2, and Th17 cytokines was significantly increased. This preliminary study is the first to follow the cellular immune response and cytokine expression profiles in a nonhuman primate model simulating field conditions of schistosomiasis and PZQ therapy, providing a promising reference in predicting the immune response to future vaccines for schistosomiasis.